2013
DOI: 10.1016/j.enconman.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of the needle lift on the internal flow and cavitation phenomenon in diesel injector nozzles by CFD using RANS methods

Abstract: Elsevier Salvador, FJ.; Martínez López, J.; Caballer Fernández, M.; Alfonso Laguna, CD. (2013). Study of the influence of the needle lift on the internal flow and cavitationphenomenon in diesel injector nozzles by CFD using RANS methods. Energy Conversion and Management. 66:246-256. doi:10.1016/j.enconman.2012.10 ABSTRACTIt is well known that cavitation phenomenon in diesel injector nozzles has a strong influence on the internal flow during the injection process and spray development.However, its influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 38 publications
3
79
0
Order By: Relevance
“…However, the influence of the needle lift on the injection process was already studied by the authors in [19]. …”
Section: Comparison In Terms Of Cavitation Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of the needle lift on the injection process was already studied by the authors in [19]. …”
Section: Comparison In Terms Of Cavitation Morphologymentioning
confidence: 99%
“…As seen in Figure 10, the area coefficient takes values equal to one in non-cavitating conditions ([15] [19]). Therefore, for these conditions, the velocity coefficient values equal the discharge coefficient ones.…”
Section: Area and Velocity Coefficientsmentioning
confidence: 99%
“…More recent studies have shown the value of CFD when determining the effects of water hammer in pipes [8]. Further, CFD have been used successfully to model cavitation and the risk of cavitation erosion in diesel injectors [9,10] and hydraulic valves [11,12]. However, the cavitation in these studies is a consequence of the accelerated flow and cavitation as the result of hydraulic transients has not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is well known that the nozzle geometric parameters have a great influence on the spray behavior, as experimentally proved by Desantes et al (2005) and Bermúdez et al (2005) and computationally reproduced by Salvador et al (2013). Thus, coupling internal and external flow simulations leads to a better representation of reality.…”
Section: Introductionmentioning
confidence: 99%